A comparative study of characteristics in diploid and tetraploid Anoectochilus roxburghii - Huang, Xiaoling; Ouyang, Kunxi; Luo, Yongzhi; Xie, Guohong; Yang, Yuesheng; Zhang, Junjie (Frontiers in Nutrition, 2022)
Artificial induction of polyploidy is an efficient technique for improving biological properties and developing new varieties of many plants. In the study presented here we analyzed and compared differences in characteristics (morphological and biological) of diploid and tetraploid Anoectochilus roxburghii plants. We found significant differences between tetraploid plants and their diploid counterparts. The tetraploid plants exhibited dwarfing and stockiness. They were also bigger and had more voluminous roots, and larger stomata, than the diploid plants. Moreover, biochemical analyses showed that contents of some amino acids and mineral elements were significantly higher in tetraploid plants. The chlorophyll content of the leaves exhibited no definitive changes, but photosynthetic performance was higher in the tetraploid plants. In addition, contents of major bioactive compounds, kinsenoside and some flavonoids, were enhanced in tetraploids. This is the first detailed analysis of morphological and biological characteristics in diploid and tetraploid A. roxburghii plants, and the results may facilitate breeding programs with the species.